STREAM SEDIMENT RECONNAISSANCE SURVEY OF NGABAHI AREA, SOUTH OF MUBI, NORTH EASTERN NIGERIA: IMPLICATIONS FOR MINERAL EXPLORATION - ABBA AHMED , HAFIZULLAH; GARBA, IBRAHIM (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2023)
The occurrence of ilmenite fragments around Ngabahi in southern Mubi, prompted this work. The aim of this study is to delineate potential areas of ilmenite and other economic mineralization in the area. Mubi is located in northeastern Nigeria within the Hawal Massif of Eastern Nigeria Terrain (ENT). The geology of the area consists predominantly of Pan African granite with rhyolitic and basaltic extrusions. Forty-seven (47) stream sediment samples were collected and analysed for 49 elements using ICP and INAA analytical techniques. The results show that ten (10) trace elements, namely Pb, Ba, Be, Mn, Rb, Y, Hf, Th, U, Ta in addition to Fe, have concentrations above the Average Universal Crustal Abundance (AUCA), and were subjected to statistical treatment. Median values of U, Th, Ta, Hf, Mn, Rb, Ba and Mn are well above the AUCA. Pearson correlation coefficients show that significant correlation exists among Fe-Mn and U-Th-Ta-Mn-Y-Hf. Though, no significant concentration of ilmenite has been observed, the dispersion train however, indicates anomalous concentrations of U, Th, Ta, Mn, Ba, Rb, Hf and Y, suggesting that the area is favourable for mineralization of lithophile (granitoid) affinity. Findings of the survey result in the delineation of some prospective targets for mineral deposits. Targets for this mineralization include the Sabongari region and the areas with anomalous metallic values, particularly Hf, Y and Rb, revealed by the stream sediments geochemical survey. All these, coupled with the favourable geology, make the study area of great potential value for economic mineralization.